Neutral Organic Super Electron Donors Made Catalytic. Issue 33 (10th July 2019) - Rohrbach, Simon; Shah, Rushabh S.; Tuttle, Tell; Murphy, John A.
Abstract: Neutral organic super electron donors (SEDs) display impressive reducing power but, until now, it has not been possible to use them catalytically in radical chain reactions. This is because, following electron transfer, these donors form persistent radical cations that trap substrate‐derived radicals. This paper unlocks a conceptually new approach to super electron donors that overcomes this issue, leading to the first catalytic neutral organic super electron donor. Abstract : CatalySED ! An organocatalytic role for a benzimidazolium salt in radical chemistry is reported. A highly reducing intermediate (−1.86 V vs. SCE) is produced simply by treatment with NaBH4 and then using air as initiator. This is the first time that an organic super electron donor has been used catalytically, which introduces a novel catalytic approach for the upconversion of reducing power.